America's working women: A documentary history, 1600 to the present - Baxandall, (1939- ...)., Rosalyn Fraad; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Accessible en ligne : https://archive.org/details/isbn_9780393312621
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

Existe-t-il une musique dite féministe ? - Lefebvre, Marie-Thérèse (Les bâtisseuses de la Cité : actes du Colloque Les Bâtisseuses de la Cité dans le cadre de la Section d'études féministes du Congrès de l'Acfas 1992, 1993)
https://cap.banq.qc.ca/notice?id=p%3A%3Ausmarcdef_0005389009&locale=fr
Keywords: 1600-1699; 1700-1799; 1900-1999; DIG; amérique du nord; amériques; arts; canada; discipline; femmes* artistes; histoire et politique; musique; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

Histoire des femmes en Occident - Duby, Georges; Perrot, Michelle (Plon, 1991)
Projet démesuré que de couvrir près de vingt siècles d'histoire du monde antique gréco-romain, de parcourir un espace qui va des rivages de la Méditerranée à ceux des mers du Nord, des colonnes d'Héraklès aux rives de l'Indus, de se plonger dans des documents aussi divers que les tombes d'une nécropole, la stèle inscrite plaquée aux murs du sanctuaire, le rouleau de papyrus, la scène peinte sur la panse d'un vase... et une littérature grecque et latine qui, si elle n'a pas donné la parole aux femmes, a beaucoup parlé d'elles. On l'aura deviné, ce livre n'a pas pour fonction de remplacer l'énorme production qui existe en ce domaine. Il aborde un petit nombre seulement des questions qui nous ont paru importantes pour aider à comprendre la place des femmes dans le monde antique et, plus encore peut-être, dans la perspective d'un ensemble de volumes traitant de l'histoire des femmes, comprendre les fondements d'habitudes mentales, de mesures juridiques, d'institutions sociales qui ont duré des siècles en Occident.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; amérique du nord; amériques; antiquité; approches et analyses; conditions des femmes*; cours; discipline; europe; his4330; histoire; histoire des femmes*; histoire et politique; incontournable; lit3220; moyen-âge; occident; oui; outils; ouvrages de références; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques

La création musicale des femmes au Québec - Lefebvre, Marie-Thérèse (Les éditions du remue-ménage, 1991)
Connues principalement comme pédagogues et interprètes, les femmes en musique ont mis du temps à se faire reconnaître dans le domaine de la composition. C’est ce volet encore ignoré de notre histoire que La Création musicale des femmes au Québec nous fait découvrir, depuis l’apport des communautés religieuses en Nouvelle-France jusqu’aux expérimentations électroacoustiques des vingt dernières années, du phénomène culturel de la musique de salon au début du siècle aux performances multimédias de nos contemporaines…
https://www.editions-rm.ca/livres/la-creation-musicale-des-femmes-au-quebec/
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; DIG; amériques; arts; biographie; discipline; femmes* artistes; femmes* compositrices; musique; périodes historiques; québec; régions géographiques; thématiques; travail

The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Verso, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis

La naissance et la petite enfance en Nouvelle Angleterre à l'époque coloniale 1630-1750 - Bergamasco-Lenarda, Lucia (Revue d’histoire moderne et contemporaine, 1984)
Keywords: 1600-1699; 1700-1799; amériques; approches et analyses; colonialisme; colonisation britannique; condition de l'enfant; cours; discipline; enfance; famille; his4443; histoire; maternité; patriarcat; petite enfance; premier cycle; périodes historiques; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Maitresses de maison, maitresses d'ecole: femmes, famille et education dans l'histoire du Quebec - Fahmy-eid, Nadia; Barry, Francine (Boréal Express, 1983)
Recueil de quatorze études, par douze spécialistes, sur des aspects des rapports entre les femmes et l'éducation, et les femmes et la famille à diverses époques de l'histoire du Québec. Un bilan des recherches sur les questions précède ces études.
Keywords: 1600-1699; 1700-1799; 1800-1899; amérique du nord; amériques; approches et analyses; canada; cours; discipline; famille; his4523; histoire; histoire des femmes*; histoire et politique; patriarcat; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; éducation

Feminism and art history: questioning the litany - Broude, Norma; Garrard, Mary D. (Harper & Row, 1982)
A long-needed corrective and alternative view of Western art history, these seventeen essays by respected scholars are arranged chronologically and cover every major period from the ANcient 2gypt to the present. While several of the essays deal with major woman artists, the book is essentially about western art history and the extent to which it has been distorted, in every period, by sexual bias. With 306 illustrations.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; Feminism and art; Feminism in art; amérique du nord; amériques; antiquité; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; occident; premier cycle; périodes historiques; régions géographiques; thématiques

Femmes peintres: 1550-1950 - Harris, Ann Sutherland; Nochlin, Linda (Ed. des femmes, 1981)
Catalogue d'exposition. Il s'agit de la première exposition rassemblant les oeuvres de femmes peintres, organisée au Los Angeles Country Museum of Art par Ann Sutherland Harris, conservateur au Metropolitan Museum of Art de New York et Linda Nochlin, enseignante en histoire de l'art à l'université de Vassar. Ces oeuvres jusque-là dispersées dans divers musées et collections privées, et rassemblées dans cette exposition et ce catalogue devenu un ouvrage de référence, font apparaître la place des femmes et leur influence parfois marquante dans l'histoire de l'art occidental. D'Italie en Flandres, en France, en Allemagne, en URSS, aux États-Unis, la vie et l'oeuvre de : Catherina Van Hemessen, Sofonisba Anguissola, Fede Galizia, Judith Leyster, Clara Peeters, Élisabeth Vigée Le Brun, Rosa Bonheur, Sonia Delaunay... Et bien d'autres.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amérique du nord; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; incontournable; peinture; premier cycle; périodes historiques; régions géographiques; thématiques

Capitalisme, Patriarcat et ségrégation professionnelle des sexes - Hartmann, Heidi; Coryell, Rosette (Questions Féministes, 1978)
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amérique du nord; amériques; angleterre; approches et analyses; capitalisme; corps; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc1016; sociologie; systèmes d'oppressions; thématiques; travail; états-unis